ANIMALISTIC IMAGES IN KARAKALPAK FOLKLORE AND WRITTEN LITERATURE - Rzaeva, R.K. (FAN va JAMIYAT, 2020)
The article deals with the issues of using names of animals in Karakalpak folklore on the example of proverbs and sayings and written literature. Using mainly the names of domestic animals is explained by the fact that the Karakapak people were engaged in cattle-breeding from ancient times. The comparative study with other languages (Russian and English) proves the statement that names of animals reflect the national peculiarities and culture of the people.